DEVELOPMENT OF THE BIOECONOMY IN UKRAINE: ADAPTING EUROPEAN EXPERIENCE FOR INTEGRATION INTO THE EUROPEAN ECONOMIC SPACE (INNOVATIVE ECONOMY, 2024)
Belova I.M., Yaroshchuk O.V. DEVELOPMENT OF THE BIOECONOMY IN UKRAINE: ADAPTING EUROPEAN EXPERIENCE FOR INTEGRATION INTO THE EUROPEAN ECONOMIC SPACEPurpose. The aim of the study is to analyse European experience in developing the bioeconomy, identify its key support instruments and substantiate the need to adapt these approaches in Ukraine to facilitate integration into the European economic space.Methodology of research. A systemic approach was employed along with methods of analysis and synthesis to evaluate European strategies in the field of bioeconomy. Comparative analysis was used to assess the feasibility of adapting European practices to the Ukrainian context.Findings. The study examined the main directions for the development of the bioeconomy in the EU, including financial, regulatory, and innovative support instruments. It was found that strategic initiatives such as the European Green Deal, the Horizon 2020 program, and Horizon Europe create favourable conditions for the sustainable use of biological resources and the promotion of innovation. Recommendations are provided for adapting these European approaches in Ukraine, particularly in the sectors of bioenergy, agriculture, and waste management. Additionally, the prospects for Ukraine’s participation in international programs aimed at supporting the bioeconomy were identified.Originality. For the first time, the necessity for a comprehensive implementation of European support mechanisms for the bioeconomy in Ukraine has been substantiated as a means to integrate the national system into the European economic space. The study demonstrates that utilizing tools such as regulatory harmonization, financing innovative projects, and developing the biotechnology sector can enhance the competitiveness of the national economy. Moreover, the methodological approach to assessing Ukraine’s bioeconomy potential has been refined by incorporating natural, economic, and social factors.Practical value. The obtained findings of this research can be used to formulate a national strategy for the development of the bioeconomy in Ukraine, adapt the regulatory framework to EU standards, develop state support programs for biotechnological enterprises, and attract international investments. The proposed measures will promote the growth of bioenergy, agricultural production, and the processing of organic waste, ensuring sustainable economic growth and environmental security. Furthermore, these results can be integrated into higher education curricula to train specialists in bioeconomy and sustainable development.Key words: bioeconomy, sustainable development, European Green Deal, innovation, bioenergy, Ukraine, Eurointegration.
Keywords: bioeconomy; sustainable development; European Green Deal; innovation; bioenergy; Ukraine; Eurointegration.